Cyanobacterial blooms in China: diversity, distribution, and cyanotoxins - Huo, Da; Gan, Nanqin; Geng, Ruozhen; Cao, Qi; Song, Lirong; Yu, Gongliang; Li, Renhui (Harmful algae, 2021)
•Plenty of studies on multi-faceted of cyanobacterial blooms have been conducted in China.•Intensity of cyanobacterial blooms in several main lake/river basins has been largely controlled.•Blooms caused by alternative bloom-forming cyanobacterial species are largely neglected. Cyanobacterial blooms, which refer to the massive growth of harmful cyanobacteria, have altered the global freshwater ecosystems during the past decades. China has the largest population in the world, and it is suffering from the harmful effect of water eutrophication and cyanobacterial blooms along with rapid development of the economy and society. Research on cyanobacterial blooms and cyanotoxins in China have been overwhelmingly enhanced and emphasized during the past decades. In the present review, the research on cyanobacterial blooms in China is generally introduced, including the history of cyanobacterial bloom studies, the diversity of the bloom-forming cyanobacteria species (BFCS), and cyanotoxin studies in China. Most studies have focused on Microcystis, its blooms, and microcystins. Newly emerging blooms with the dominance of non-Microcystis BFCS have been gradually expanding to wide regions in China. Understanding the basic features of these non-Microcystis BFCS and their blooms, including their diversity, occurrence, physio-ecology, and harmful metabolites, will provide direction on future studies of cyanobacterial blooms in China.